Child of mine - Lewis, David (David Gerald); Lewis, Beverly, 1949- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2014)
"Desperately clinging to the hope of finding her long-lost daughter, will Kelly miss out on the chance to find love--and a family--once more?"--
Keywords: Mothers of kidnapped children -- Fiction; Adopted children -- Fiction; Man-woman relationships -- Fiction; Identity (Psychology) -- Fiction; Amish -- Fiction; Ohio -- Fiction; Domestic fiction; Love stories; Love stories; Domestic fiction; Love stories